2011
DOI: 10.1093/toxsci/kfr330
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine A–Induced Oxidative Stress in Human Renal Mesangial Cells: A Role for ERK 1/2 MAPK Signaling

Abstract: Cyclosporine A (CsA) is a potent immunosuppressant used to prevent organ transplant rejection and in the treatment of autoimmune diseases. However, chronic CsA nephropathy is the major limiting factor to its widespread use. The exact mechanisms of CsA-induced renal damage remain to be fully elucidated. The objective of the current research was to examine whether CsA treatment induced any glomerular mesangial cell alterations. In this research goal, human mesangial cells (HMCs) were treated with CsA for various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 49 publications
6
25
0
Order By: Relevance
“…A high concentration of CsA, but not lovastatin, elevates ROS levels in mpkCCD c14 cells via activation of NADPH oxidase. Recent studies (9,31) have suggested that CsA elevates ROS in mesangial cells and induces apoptosis in renal epithelial LLC-PK1 cells. To examine whether a high concentration of CsA elevates ROS in distal tubular cells, mpkCCD c14 cells were stained with a ROS probe.…”
Section: Csa Increases But Lovastatin Decreases Levels Of Cholestermentioning
confidence: 99%
“…A high concentration of CsA, but not lovastatin, elevates ROS levels in mpkCCD c14 cells via activation of NADPH oxidase. Recent studies (9,31) have suggested that CsA elevates ROS in mesangial cells and induces apoptosis in renal epithelial LLC-PK1 cells. To examine whether a high concentration of CsA elevates ROS in distal tubular cells, mpkCCD c14 cells were stained with a ROS probe.…”
Section: Csa Increases But Lovastatin Decreases Levels Of Cholestermentioning
confidence: 99%
“…Cyclosporine A (CsA) is a potent immunosuppressant used for the prevention of organ transplant rejection and in the treatment of autoimmune diseases [10] has been linked with several adverse effects including toxicities (nephrotoxicity, hepatoxicity and neurotoxicity), hypertension, dyslipidemia, gingival hyperplasia, hypertrichosis, malignancies and increased risk of cardiovascular events [11], both in transplant and non-transplant settings (autoimmune disorders). Reactive oxygen species (ROS) production and oxidative stress signaling has been implicated in a variety of renal diseases such as IgA nephropathy and chronic kidney disease [10].…”
Section: Introductionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) production and oxidative stress signaling has been implicated in a variety of renal diseases such as IgA nephropathy and chronic kidney disease [10]. Indiscriminate usage of C. afer in treatment of diseases in Nigeria and many other countries justify carrying this research and many of its kind.…”
Section: Introductionmentioning
confidence: 99%
“…The activation of the MAPK pathway has been shown to be a potential mechanism involved in kidney disease. Kidney disease can be ameliorated if the MAPK signal pathway is inhibited (Pengal et al, 2011;O'Connell et al, 2012). Our results demonstrated that the MAPK pathway is abnormal in AS patients, which provides an experimental basis for further studies into AS pathogenesis.…”
Section: Discussionmentioning
confidence: 52%